Determination of the vibrational contribution to the entropy change at the martensitic transformation in Ni–Mn–Sn metamagnetic shape memory alloys: a combined approach of time-of-flight neutron spectroscopy and ab initio calculations. (27th April 2016) - Recarte, V; Zbiri, M; Jiménez-Ruiz, M; Sánchez-Alarcos, V; Pérez-Landazábal, J I
Abstract: The different contributions to the entropy change linked to the austenite-martensitic transition in a Ni–Mn–Sn metamagnetic shape memory alloy have been determined by combining different experimental techniques. The vibrational contribution has been inferred from the vibrational density of states of both the martensitic and austenite phases. This has been accomplished by combining time-of-flight neutron scattering measurements and ab initio calculations. Further, the electronic part of the entropy change has also been calculated. Since the martensitic transformation takes place between two paramagnetic phases, the magnetic contribution can be neglected and the entropy change can be reduced to the sum of two terms: vibrational and electronic. The obtained value of the vibrational contribution ( − 36 ± 5   J   kg − 1   K − 1 ) nearly provides the total entropy change measured by calorimetry ( − 41   ± 3   J   kg − 1   K − 1 ), the difference being the electronic contribution within the experimental error.